2019
DOI: 10.1021/acsami.9b15975
|View full text |Cite
|
Sign up to set email alerts
|

Design of New n-Type Porphyrin Acceptors with Subtle Side-Chain Engineering for Efficient Nonfullerene Solar Cells with Low Energy Loss and Optoelectronic Response Covering the Near-Infrared Region

Abstract: A series of tailor-made highly efficient and near-infrared (NIR) porphyrin-based acceptors is designed and synthesized for fullerene-free bulk-heterojunction (BHJ) organic solar cells. Constructing BHJ active layers using a PTB7-Th donor and porphyrin acceptors (P-x), which have complementary absorption, accomplishes panchromatic photon-to-current conversion from 300 to 950 nm. Our study shows that side chains of the porphyrin acceptors fairly influence the molecular ordering and nanomorphology of the BHJ acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…In addition, Tsai et al reported three Zn(II) porphyrin-based A-D-A conjugates having 2-(5,6-difluoro-3-oxo-2,3-dihydro-1Hinden-1-ylidene)-malononitrile as the electron-accepting end group. 53 Similar to the above examples, the three conjugates 2-8a-c are different from each other only in the structure of meso substituents of the central porphyrin unit; namely, 3,4,5tridodecyloxyphenyl for 2-8a, 2,6-didodecyloxyphenyl for 2-8b, and 3,5-di-tert-butylphenyl for 2-8c. These compounds were evaluated as n-type materials in BHJ OPVs with a p-type polymer PTB7-Th.…”
Section: Derivatives Used As N-type Materialsmentioning
confidence: 67%
“…In addition, Tsai et al reported three Zn(II) porphyrin-based A-D-A conjugates having 2-(5,6-difluoro-3-oxo-2,3-dihydro-1Hinden-1-ylidene)-malononitrile as the electron-accepting end group. 53 Similar to the above examples, the three conjugates 2-8a-c are different from each other only in the structure of meso substituents of the central porphyrin unit; namely, 3,4,5tridodecyloxyphenyl for 2-8a, 2,6-didodecyloxyphenyl for 2-8b, and 3,5-di-tert-butylphenyl for 2-8c. These compounds were evaluated as n-type materials in BHJ OPVs with a p-type polymer PTB7-Th.…”
Section: Derivatives Used As N-type Materialsmentioning
confidence: 67%
“… 46 Finally, a series of n-type Zn-porphyrins coupled with 2FIC as strong electron-withdrawing units and different functional groups at the meso positions were reported, affording 7.23% as the best PCE in devices using PTB7-Th as the donor. 47 Zhu et al reported the highest PCE reached to date (9.64%) in devices using PTB7-Th as the donor and Zn-porphyrin incorporating four PDI units as the acceptor. 48 It should be remarked that in all these molecules, the Zn-Por is the electron-donor moiety.…”
Section: Introductionmentioning
confidence: 99%
“…In photosynthesis of plants, which is also a bioenvironment, fast transfer of photogenerated electrons can be achieved through the organometallic pigment chlorophyll. , As the major component in chlorophyll, porphyrins are composed of four modified pyrrole subunits interconnected at their α carbon atoms via methine bridges. So, porphyrins are easy to modify and structure–activity relationships of porphyrin compounds have been extensively and thoroughly researched. Typically, it was reported that porphyrins with different length alkyl chains exhibit different abilities to transfer photogenerated electrons. …”
Section: Introductionmentioning
confidence: 99%